A sporadic pediatric case of a spinal dumbbell-shaped epithelioid malignant peripheral nerve sheath tumor with a novel germline mutation in SMARCB1: a case report and review of the literature - Qi, Maoyang; Jiang, Nan; Duan, Wanru; Chen, Zan (Frontiers in Neurology, 2023)
Malignant peripheral nerve sheath tumors (MPNSTs) are commonly associated with poor prognosis and are primarily caused by germline mutations in the SMARCB1/INI-1 gene. However, these tumors are rarely found in the spine. This case report presents the case of a 3-year-old boy diagnosed with a lumbosacral dumbbell-shaped epithelioid MPNST, an extremely uncommon manifestation. Immunohistochemistry revealed the complete absence of the SMARCB1/INI-1 protein, and genetic testing identified a novel germline mutation in the SMARCB1/INI-1 gene in both the patient and his father, suggesting a “second-hit loss.” One year of follow-up after the tumor's radical resection revealed no suspected metastasis. This case report offers novel genetic research results regarding spinal dumbbell-shaped MPNSTs. Six studies, including 13 cases associated with spinal dumbbell MPNST, were included in the literature. The range of age of these patients varied from 2 to 71 years. Of the 12 known patients diagnosed with spinal dumbbell MPNST, only one received radiation therapy, while the rest underwent surgery. Two patients who underwent partial resection had metastases after surgery, while one of the five patients who underwent complete surgical resection alone had no distant metastases and a good prognosis, indicating that radical resection is more likely to be effective in inhibiting distant metastasis and improving the prognosis.